Literasi Media Keluarga Desa - Hayu R, Diyah (Jurnal Komunikasi, 2010)
Media Literacy is a concept which enable audience to negotiate their own meaning when interact to media. This concept is needed because media content can be bias and inaccurate. The reality in media, especially television, does not reflect the social reality. It is constructed by the process of gate keeping and media framing. As a consequence, the reception process becomes complicated since the way audience receive the messages depends on the knowledge and skill they have.